A single-domain relaxor ferroelectric single crystal and a preparation method and application thereof

CN116334761BActive Publication Date: 2026-10-09XI AN JIAOTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310340775.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-31
Publication Date
2026-10-09
Estimated Expiration
2043-03-31

AI Technical Summary

Technical Problem

该方法对晶体的极化过程均要求缓慢的升降温,使得单畴样品的制备周期变长,同时由于PMN-PT晶体晶格常数a/c接近于1,沿晶体的自发极化方向施加电场时晶体内部会产生巨大的内应力,导致晶体开裂或在撤去电场时发生严重的退极化

Benefits of technology

[0021]This invention firstly achieves a "2T" engineered domain structure by polarizing the electric field along the non-polar axis direction during the first polarization step. Due to the low coercive electric field, the polarization vector inside the crystal undergoes a 90° domain rotation at room temperature. Analysis of the polarization orientation of the layered "2T" engineered domains and the dynamics of the domains under an applied electric field reveals that at room temperature, under a small lateral external electric field, domains with an acute angle between their polarization direction and the applied electric field direction (referred to as co-directional domains) expand, while domains with an obtuse angle between their polarization direction and the applied electric field direction (referred to as anti-directional domains) contract. When the co-directional domains expand to a certain extent, the anti-directional domains disappear, and adjacent co-directional domains fuse to achieve a single-domain state. This method overcomes the problems of incomplete single-domain formation and crystal cracking caused by insufficient internal stress release in traditional single-domain formation processes, avoids the slow annealing pretreatment process and high-temperature polarization, and simplifies the process flow. This method enables the high degree of single-domain formation of high-performance multi-domain ferroelectric single crystals, and the resulting samples exhibit stable optical properties. On the one hand, the single-domain PMN-PT-based crystals have high optical transmittance and nonlinear optical properties that are far superior to those of materials such as BBO, KTP, and LiNbO3. On the other hand, the successful preparation of single-domain PMN-PT-based relaxor ferroelectric single crystals lays the material foundation for the development of femtosecond-written relaxor ferroelectric photonic crystals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116334761B_ABST
    Figure CN116334761B_ABST
Patent Text Reader

Abstract

The application discloses a single-domain state relaxor ferroelectric single crystal and a preparation method and application thereof, S1, electrodes are plated on two side surfaces perpendicular to two short edges of an optical surface of a cuboid relaxor ferroelectric single crystal, and then polarization treatment is carried out at room temperature to obtain an engineered domain relaxor ferroelectric single crystal; S2, electrodes are plated on two side surfaces perpendicular to two long edges of an optical surface of the engineered domain relaxor ferroelectric single crystal, and then polarization treatment is carried out at room temperature to obtain a single-domain state relaxor ferroelectric single crystal. The process flow is simplified, high-performance multi-domain ferroelectric single crystals are highly monodomainized, and the obtained sample has stable optical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of optical crystals and their applications, and relates to a single-domain relaxed ferroelectric single crystal, its preparation method and application. Background Technology

[0002] The fabrication of acoustic / photonic crystals using domain flipping has attracted increasing attention in recent years. Compared to purely elastic phononic crystals composed of different materials with varying elastic moduli and / or mass densities, domain-flipped phononic crystals achieve phonon control by manipulating the orientation of domains within a single ferroelectric body, making them more advantageous for the fabrication of surface acoustic wave (SAW) devices. Domain flipping can also achieve spatial modulation of second-order nonlinear optical coefficients; these crystals are called domain-flipped nonlinear photonic crystals or optical superlattices.

[0003] Femtosecond lasers can be used to successfully write artificial domain structures into single-domain or multi-domain crystals within a single domain region. Currently, the writing of periodic domain arrays and waveguide structures within the single-domain crystal LiNbO3 has been successfully achieved, marking the initial realization of the fabrication of three-dimensional phononic and photonic crystals. The fabrication of three-dimensional acoustic / photonic crystals via femtosecond laser writing requires uniform domain orientation in the writing region, i.e., the crystal must be in a single-domain state. Therefore, the fabrication of single-domain crystals is the material basis for the fabrication of phononic / photonic crystals.

[0004] The transmittance of single-domain transparent PMN-PT single crystals can reach over 68% in the range of 0.4-5μm. Its effective electro-optic coefficient (γc = 112 pm / V) is 5 times that of lithium niobate crystals, and its effective nonlinear optical coefficient is 2-4 times that of LiNbO3. Furthermore, its resistance to photodamage is 2-6 times that of LiNbO3 (PMN-PT ~ 500 MW / cm²). 2 However, the optical performance of engineered domain crystals is far inferior to that of single-domain crystals, making it difficult to meet the requirements of electro-optic and nonlinear optical device applications. From the perspectives of both phonon / photonic crystal fabrication and electro-optic and nonlinear optical device applications, single-domain fabrication processes are essential for the development of optical applications of PMN-PT-based crystals.

[0005] Relaxor ferroelectric single crystals possess multiple spontaneous polarization directions. During single-domain formation, significant internal stress is generated within the crystal, making it prone to cracking. Current methods for single-domain formation require the crystal to undergo prolonged high-temperature annealing, followed by slow heating of the electrode-coated crystal to 150°C in a polarization apparatus. A DC electric field is then applied along the spontaneous polarization direction, followed by a slow reduction of the DC electric field strength to zero, while the crystal is cooled to room temperature at a rate of 0.5-2°C / min, thus obtaining a single-domain crystal. This method requires slow heating and cooling during the polarization process, lengthening the preparation cycle of single-domain samples. Furthermore, because the lattice constant a / c of ​​PMN-PT crystals is close to 1, significant internal stress is generated within the crystal when an electric field is applied along the spontaneous polarization direction, leading to crystal cracking or severe depolarization upon removal of the electric field. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a single-domain relaxed ferroelectric single crystal, its preparation method and application, which simplifies the process flow, realizes the high degree of single-domain formation of high-performance multi-domain ferroelectric single crystal, and the obtained sample has stable optical properties.

[0007] To achieve the above objectives, the present invention employs the following technical solution:

[0008] A method for preparing a single-domain relaxed ferroelectric single crystal includes the following steps:

[0009] S1, electrodes are deposited on the two sides perpendicular to the two short sides of the optical surface of the cuboid relaxor ferroelectric single crystal, and then polarization treatment is performed at room temperature to obtain the engineered domain relaxor ferroelectric single crystal.

[0010] S2, electrodes are deposited on the two sides perpendicular to the two long sides of the optical surface of the engineered domain relaxor ferroelectric single crystal, and then polarization treatment is performed at room temperature to obtain a single-domain relaxor ferroelectric single crystal.

[0011] Preferably, before S1, the cuboid relaxor ferroelectric single crystal is annealed.

[0012] Furthermore, the annealing process is as follows: the cuboid relaxor ferroelectric single crystal is heated to 200-600℃ at a rate of 2-4℃ / min, held at that temperature for 5 hours, and then cooled to room temperature at a rate of 0.5-2℃ / min.

[0013] Preferably, the specific process of S1 is as follows: electrodes are sputtered on two sides perpendicular to the two short sides of the optical surface of the cuboid relaxor ferroelectric single crystal; a DC electric field is applied to the cuboid relaxor ferroelectric single crystal at room temperature, with an electric field strength of 0.3-1 kV / mm, a voltage application rate of 3-50 V / min, a voltage holding time of 5-30 minutes, and then the voltage is removed at a voltage reduction rate of 3-50 V / min.

[0014] Preferably, the specific process of S2 is as follows: remove the electrodes on the engineered domain relaxor ferroelectric single crystal, sputter electrodes on two sides perpendicular to the two long sides of the optical surface of the engineered domain relaxor ferroelectric single crystal, apply a DC electric field to the engineered domain relaxor ferroelectric single crystal at room temperature with an electric field strength of 0.1-0.2 kV / mm, a voltage application rate of 3-10 V / min, hold the voltage for 5-30 minutes, then remove the voltage at a voltage reduction rate of 3-50 V / min, and then remove the electrodes.

[0015] Preferably, the relaxor ferroelectric single crystal in S1 is a binary (1-x)Pb(Mg) 1 / 3 Nb 2 / 3 Relaxor ferroelectric single crystals of O3-xPbTiO3 system, ternary (1-xy)Pb(In) 1 / 2 Nb 1 / 2 O3-xPb(Mg) 1 / 3 Nb 2 / 3 Relaxor ferroelectric single crystals of O3-yPbTiO3 system or rare earth-doped binary and ternary system relaxor ferroelectric single crystals.

[0016] Preferably, the optical surface flatness of the relaxor ferroelectric single crystal in S1 is less than 1 μm.

[0017] Preferably, the length of the relaxor ferroelectric single crystal in S1 is 2-10 mm, the width is 2-6 mm, and the height is 0.5-3 mm.

[0018] A single-domain relaxed ferroelectric single crystal prepared by the method described above.

[0019] The application of the single-domain relaxed ferroelectric single crystal in three-dimensional phonon or photonic crystals.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] This invention firstly achieves a "2T" engineered domain structure by polarizing the electric field along the non-polar axis direction during the first polarization step. Due to the low coercive electric field, the polarization vector inside the crystal undergoes a 90° domain rotation at room temperature. Analysis of the polarization orientation of the layered "2T" engineered domains and the dynamics of the domains under an applied electric field reveals that at room temperature, under a small lateral external electric field, domains with an acute angle between their polarization direction and the applied electric field direction (referred to as co-directional domains) expand, while domains with an obtuse angle between their polarization direction and the applied electric field direction (referred to as anti-directional domains) contract. When the co-directional domains expand to a certain extent, the anti-directional domains disappear, and adjacent co-directional domains fuse to achieve a single-domain state. This method overcomes the problems of incomplete single-domain formation and crystal cracking caused by insufficient internal stress release in traditional single-domain formation processes, avoids the slow annealing pretreatment process and high-temperature polarization, and simplifies the process flow. This method enables the high degree of single-domain formation of high-performance multi-domain ferroelectric single crystals, and the resulting samples exhibit stable optical properties. On the one hand, the single-domain PMN-PT-based crystals have high optical transmittance and nonlinear optical properties that are far superior to those of materials such as BBO, KTP, and LiNbO3. On the other hand, the successful preparation of single-domain PMN-PT-based relaxor ferroelectric single crystals lays the material foundation for the development of femtosecond-written relaxor ferroelectric photonic crystals. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the cuboid relaxor ferroelectric single crystal structure of the present invention;

[0023] Figure 2 This is a schematic diagram of the first polarization of the present invention;

[0024] Figure 3 This is the polarization pattern after the first polarization of the present invention;

[0025] Figure 4 This is a schematic diagram of the second polarization of the present invention;

[0026] Figure 5 This is the polarization pattern after the second polarization of the present invention;

[0027] Figure 6 This is a comparison diagram of the optical transmittance properties of the unpolarized and single-domain relaxed ferroelectric single crystals of the present invention. Detailed Implementation

[0028] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0029] It should be noted that the terms “front,” “back,” “left,” “right,” “up,” and “down” used in the following description refer to the directions shown in the attached diagrams, while the terms “inner” and “outer” refer to the directions toward or away from the geometric center of a specific component, respectively.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0031] The present invention discloses a method for preparing single-domain relaxor ferroelectric single crystals, wherein the single crystal is a binary PMN-PT system relaxor ferroelectric single crystal, a ternary PIN-PMN-PT system relaxor ferroelectric single crystal, or a rare-earth-doped binary or ternary system relaxor ferroelectric single crystal. First, an engineered domain structure is obtained through room-temperature DC polarization. Then, a low electric field is applied in the perpendicular direction to induce domain wall movement and fusion of adjacent domains to achieve single-domain formation of the crystal.

[0032] Specifically, the process includes the following:

[0033] 1. Crystal processing.

[0034] Regions with high compositional uniformity were selected from relaxor ferroelectric single crystals and oriented in three dimensions to obtain tetragonal single crystals with the

[011] crystal orientation. These were then cut into experimental shapes of (2-10)×(2-6)×(0.5-3) mm (a×b×c). Plane 1 and its parallel planes were ground and polished, as shown below. Figure 1 As shown. Gently grind with sandpaper until there are no obvious scratches, then polish on a polishing machine until it is close to an optical plane (flatness less than 1 micrometer) to obtain the sample required for the experiment.

[0035] The tetragonal single crystal was cut into three sections along

[110] ,

[001] , and

[110] respectively. The cuboid has plane 1 as its optical plane.

[0036] Relaxor ferroelectric single crystals are binary (1-x)Pb(Mg) 1 / 3 Nb 2 / 3 Relaxor ferroelectric single crystals of O3-xPbTiO3 system, ternary (1-xy)Pb(In) 1 / 2 Nb 1 / 2 O3-xPb(Mg) 1 / 3 Nb 2 / 3 Relaxor ferroelectric single crystals of O3-yPbTiO3 system or rare earth-doped binary and ternary system relaxor ferroelectric single crystals.

[0037] 2. Annealing

[0038] 2.1 Anneal the tetragonal single crystal with the

[011] crystal orientation described in step 1 by heating it to 200-600℃ at a rate of 2-4℃ / min and holding it at that temperature for 5-10 hours.

[0039] 2.2 Cool the crystal described in step 2.1 to room temperature at a rate of 0.5-2℃ / min.

[0040] 3. First polarization.

[0041] 3.1 Sputtering electrodes, including gold electrodes and silver electrodes, on the two sides perpendicular to the two short sides of the optical surface of the relaxor ferroelectric single crystal sample, i.e., the crystal plane 2 obtained in step 2 above and the plane parallel to it (i.e. the plane perpendicular to the

[110] direction), with a thickness of about 100-250 nanometers.

[0042] 3.2, such as Figure 2 As shown, the crystal described in step 3.1 is placed in a self-built polarization device and a DC electric field is applied along the

[110] direction. The electric field strength is 0.3-1 kV / mm, the pressure application rate is 3-50 V / min, and the pressure is held for 5-30 minutes.

[0043] 3.3. Slowly remove the DC electric field described in step 4.2, with a voltage reduction rate of 3-50 volts / min, and remove the crystal to obtain a

[110] polarized engineered domain ferroelectric single crystal, such as... Figure 3 As shown.

[0044] 4. Second polarization.

[0045] Step 4.1: Wipe or grind away the crystal plane 2 and the electrode sputtered on the plane parallel to it (i.e. the plane perpendicular to the

[110] direction) as described in step 3 above.

[0046] Step 4.2: As Figure 4 As shown, for the two side surfaces perpendicular to the two long sides of the optical surface, namely plane 3 of the relaxor ferroelectric single crystal obtained in step 4.1 and the plane parallel to it (i.e., perpendicular to it), (Planar sputtering electrode) with a thickness of approximately 100-250 nanometers, including gold or silver electrodes.

[0047] Step 4.3: Apply an edge-to-edge coating to the crystal obtained in step 4.2. A DC electric field with an electric field strength of 0.1-0.2 kV / mm and a pressurization rate of 3-10 V / min.

[0048] Step 4.4: Due to the special nature of the domain structure, the domain walls of the crystal will move under the action of an external electric field, and adjacent domains will merge. This method yields a single-domain relaxed ferroelectric single crystal, such as... Figure 5 As shown.

[0049] Step 4.5: Slowly remove the voltage at a rate of 3-50 volts / minute, and place plane 3 and the plane parallel to it (i.e., perpendicular to it) Electrodes sputtered in a plane (direction) are wiped or ground off.

[0050] This invention analyzes the dynamic process of electric domains under an applied electric field and proposes a new method for preparing single-domain crystals—the two-step polarization method—by controlling the movement and fusion of domain walls within engineered domain crystals. Firstly, in the first polarization step (polarization along the

[110] direction), the process is the same as that for preparing engineered domain ferroelectric single crystals. When the electric field is polarized along the non-polar axis direction, due to the lower coercive electric field, the original

[001] direction within the crystal...

[010] 、

[100] 、 and The polarization vector of the direction undergoes a 90° domain rotation at room temperature to the

[100] and

[010] directions, resulting in a "2T" engineered domain structure. Analysis of the polarization orientation of the layered "2T" engineered domains and the dynamics of the domains under an applied electric field reveals that at room temperature, under a small lateral external electric field, domains with polarization directions at acute angles to the applied electric field direction (referred to as co-directional domains) expand, while domains with polarization directions at obtuse angles to the applied electric field direction (referred to as anti-directional domains) contract. When the co-directional domains expand to a certain extent, the anti-directional domains disappear, and adjacent co-directional domains fuse to form a single-domain crystal.

[0051] This method overcomes the problems of incomplete single-domain formation and crystal cracking caused by insufficient internal stress release in traditional single-domain formation processes. It avoids the slow annealing pretreatment process and high-temperature polarization, simplifying the process flow. This method enables the high degree of single-domain formation of high-performance multi-domain ferroelectric single crystals, and the resulting samples exhibit stable optical properties: on the one hand, the single-domain PMN-PT-based crystals have very high optical transmittance and performance parameters far superior to materials such as BBO, KTP, and LiNbO3; on the other hand, the successful preparation of single-domain PMN-PT-based relaxor ferroelectric single crystals lays the material foundation for the development of femtosecond-written relaxor ferroelectric photonic crystals.

[0052] Example 1

[0053] 1. Crystal processing.

[0054] 1.1 Select a binary PMN-PT crystal region with high compositional uniformity and orient it in three dimensions to obtain a tetragonal single crystal with the

[011] crystal orientation. Cut it into the required shape of 10×2×1 mm (a×b×c). Grind and polish plane 1 and its parallel planes. Grind gently with sandpaper until there are no obvious scratches, and then polish it on a polishing machine until it is close to an optical plane (flatness less than 1 micrometer) to obtain the sample required for the experiment.

[0055] 2. Annealing.

[0056] 2.1 The tetragonal single crystal sample with the

[011] crystal orientation described in step 1 is annealed by heating to 600°C at a rate of 4°C / min and holding for 8 hours.

[0057] 2.2 Cool the crystal described in step 2.1 to room temperature at a rate of 0.5℃ / min.

[0058] 3. First polarization.

[0059] 3.1. In step 2 above, a gold electrode is sputtered onto the crystal plane 2 and the plane parallel to it (i.e. the plane perpendicular to the

[110] direction) with a thickness of about 100 nanometers.

[0060] 3.2 Place the crystal described in step 3.1 in a self-built polarization device and apply a DC electric field along the

[110] direction. The electric field strength is 0.3 kV / mm, the pressure application rate is 3 V / min, and the pressure is maintained for 30 minutes.

[0061] 3.3. Slowly remove the DC electric field described in step 4.2 at a voltage reduction rate of 3 volts / minute, remove the crystal, and obtain an engineering domain ferroelectric single crystal with

[110] polarization.

[0062] 4. Second polarization

[0063] Step 4.1: Wipe or grind away the crystal plane 2 and the electrode sputtered on the plane parallel to it (i.e. the plane perpendicular to the

[110] direction) as described in step 3 above.

[0064] Step 4.2: Plane 3 of the relaxor ferroelectric single crystal obtained in Step 4.1 and the plane parallel to it (i.e., perpendicular to it). Gold electrodes are sputtered onto a plane with a thickness of approximately 100 nanometers.

[0065] Step 4.3: Apply an edge-to-edge coating to the crystal obtained in step 4.2. A DC electric field with a field strength of 0.2 kV / mm and a pressurization rate of 10 V / min.

[0066] Step 4.4: Due to the special nature of the domain structure, the domain walls of the crystal will move under the action of an external electric field, and adjacent domains will merge. This method can be used to obtain a single-domain relaxed ferroelectric single crystal.

[0067] Step 4.5: Slowly remove the voltage at a rate of 10 volts per minute, and place plane 3 and the plane parallel to it (i.e., perpendicular to it) Electrodes sputtered in a plane (direction) are wiped or ground off.

[0068] like Figure 6As shown, the optical transmittance of the unpolarized tetragonal single crystal and the single-domain crystal after Example 1 are compared. The optical transmittance of the single-domain crystal is increased from 50% to 65%.

[0069] Example 2

[0070] 1. Crystal processing.

[0071] 1.1 Select a PIN-PMN-PT crystal region with high compositional uniformity and orient it in three dimensions to obtain a tetragonal single crystal with the

[011] crystal orientation. Cut it into the shape required for the experiment, 2×6×0.5 mm (a×b×c). Grind and polish plane 1 and its parallel planes. Grind gently with sandpaper until there are no obvious scratches. Then polish it on a polishing machine until it is close to the optical plane (flatness less than 1 micrometer) to obtain the sample required for the experiment.

[0072] 2. Annealing.

[0073] 2.1 The PIN-PMN-PT tetragonal phase relaxor ferroelectric single crystal sample with the

[011] crystal orientation described in step 1 is subjected to annealing treatment, and the temperature is increased to 200℃ at a rate of 2℃ / min and held for 10 hours.

[0074] 2.2 Cool the crystal described in step 2.1 to room temperature at a rate of 0.5℃ / min.

[0075] 3. First polarization.

[0076] 3.1. In step 2 above, a gold electrode is sputtered onto the crystal plane 2 and the plane parallel to it (i.e. the plane perpendicular to the

[110] direction) with a thickness of about 100 nanometers.

[0077] 3.2 Place the crystal described in step 3.1 in a self-built polarization device and apply a DC electric field along the

[110] direction. The electric field strength is 1 kV / mm, the pressure application rate is 50 V / min, and the pressure is held for 5 minutes.

[0078] 3.3. Slowly remove the DC electric field described in step 4.2 at a voltage reduction rate of 50 volts / min, remove the crystal, and obtain an engineering domain ferroelectric single crystal with

[110] polarization.

[0079] 4. Second polarization

[0080] Step 4.1: Wipe or grind away the crystal plane 2 and the electrode sputtered on the plane parallel to it (i.e. the plane perpendicular to the

[110] direction) as described in step 3 above.

[0081] Step 4.2: Plane 3 of the relaxor ferroelectric single crystal obtained in Step 4.1 and the plane parallel to it (i.e., perpendicular to it). Gold electrodes are sputtered onto a plane with a thickness of approximately 100 nanometers.

[0082] Step 4.3: Apply an edge-to-edge coating to the crystal obtained in step 4.2. A DC electric field with a field strength of 0.1 kV / mm and a pressurization rate of 3 V / min.

[0083] Step 4.4: Due to the special nature of the domain structure, the domain walls of the crystal will move under the action of an external electric field, and adjacent domains will merge. This method can be used to obtain a single-domain relaxed ferroelectric single crystal.

[0084] Step 4.5: Slowly remove the voltage at a rate of 3 volts per minute, and place plane 3 and the plane parallel to it (i.e., perpendicular to it) Electrodes sputtered in a plane (direction) are wiped or ground off.

[0085] Example 3.

[0086] 1. Crystal processing.

[0087] 1.1 Select a samarium-doped PMN-PT crystal region with high compositional uniformity and orient it in three dimensions to obtain a tetragonal single crystal with the

[011] crystal orientation. Cut it into the required shape of 8×5×0.5 mm (a×b×c). Grind and polish plane 1 and its parallel planes. Grind gently with sandpaper until there are no obvious scratches, and then polish it on a polishing machine until it is close to an optical plane (flatness less than 1 micrometer) to obtain the sample required for the experiment.

[0088] 2. Annealing.

[0089] 2.1 The PIN-PMN-PT tetragonal phase relaxor ferroelectric single crystal sample with the

[011] crystal orientation described in step 1 is subjected to annealing treatment, and the temperature is increased to 300℃ at a rate of 2℃ / min and held for 6 hours.

[0090] 2.2 Cool the crystal described in step 2.1 to room temperature at a rate of 2°C / minute.

[0091] 3. First polarization.

[0092] 3.1. In step 2 above, a gold electrode is sputtered onto the crystal plane 2 and the plane parallel to it (i.e. the plane perpendicular to the

[110] direction) with a thickness of about 100 nanometers.

[0093] 3.2 Place the crystal described in step 3.1 in a self-built polarization device and apply a DC electric field along the

[110] direction. The electric field strength is 0.6 kV / mm, the pressure application rate is 10 V / min, and the pressure is maintained for 5 minutes.

[0094] 3.3. Slowly remove the DC electric field described in step 4.2 at a voltage reduction rate of 10 volts / min, remove the crystal, and obtain an engineering domain ferroelectric single crystal with

[110] polarization.

[0095] 4. Second polarization.

[0096] Step 4.1: Wipe or grind away the crystal plane 2 and the electrode sputtered on the plane parallel to it (i.e. the plane perpendicular to the

[110] direction) as described in step 3 above.

[0097] Step 4.2: Plane 3 of the relaxor ferroelectric single crystal obtained in Step 4.1 and the plane parallel to it (i.e., perpendicular to it). Gold electrodes are sputtered onto a plane with a thickness of approximately 100 nanometers.

[0098] Step 4.3: Apply an edge-to-edge coating to the crystal obtained in step 4.2. A DC electric field with a field strength of 0.1 kV / mm and a pressurization rate of 3 V / min.

[0099] Step 4.4: Due to the special nature of the domain structure, the domain walls of the crystal will move under the action of an external electric field, and adjacent domains will merge. This method can be used to obtain a single-domain relaxed ferroelectric single crystal.

[0100] Step 4.5: Slowly remove the voltage at a rate of 3 volts per minute, and place plane 3 and the plane parallel to it (i.e., perpendicular to it) Electrodes sputtered in a plane (direction) are wiped or ground off;

[0101] Example 4

[0102] 1. Crystal processing.

[0103] 1.1 Select a samarium-doped PIN-PMN-PT crystal region with high compositional uniformity and orient it in three dimensions to obtain a tetragonal single crystal with the

[011] crystal orientation. Cut it into the shape required for the experiment, 5×5×2 mm (a×b×c). Grind and polish plane 1 and its parallel planes. Grind it gently with sandpaper until there are no obvious scratches. Then polish it on a polishing machine until it is close to the optical plane (flatness is less than 1 micrometer) to obtain the sample required for the experiment.

[0104] 2. Annealing.

[0105] 2.1 The PIN-PMN-PT tetragonal phase relaxor ferroelectric single crystal sample with the

[011] crystal orientation described in step 1 is subjected to annealing treatment, and the temperature is increased to 300℃ at a rate of 1℃ / min and held for 5 hours.

[0106] 2.2 Cool the crystal described in step 2.1 to room temperature at a rate of 1°C / minute.

[0107] 3. First polarization.

[0108] 3.1. In step 2 above, a gold electrode is sputtered onto the crystal plane 2 and the plane parallel to it (i.e. the plane perpendicular to the

[110] direction) with a thickness of about 100 nanometers.

[0109] 3.2 Place the crystal described in step 3.1 in a self-built polarization device and apply a DC electric field along the

[110] direction. The electric field strength is 0.6 kV / mm, the pressure application rate is 10 V / min, and the pressure is maintained for 5 minutes.

[0110] 3.3. Slowly remove the DC electric field described in step 4.2 at a voltage reduction rate of 10 volts / min, remove the crystal, and obtain an engineering domain ferroelectric single crystal with

[110] polarization.

[0111] 4. Second polarization.

[0112] Step 4.1: Wipe or grind away the crystal plane 2 and the electrode sputtered on the plane parallel to it (i.e. the plane perpendicular to the

[110] direction) as described in step 3 above.

[0113] Step 4.2: Plane 3 of the relaxor ferroelectric single crystal obtained in Step 4.1 and the plane parallel to it (i.e., perpendicular to it). Gold electrodes are sputtered onto a plane with a thickness of approximately 100 nanometers.

[0114] Step 4.3: Apply an edge-to-edge coating to the crystal obtained in step 4.2. A DC electric field with a field strength of 0.15 kV / mm and a pressurization rate of 50 V / min.

[0115] Step 4.4: Due to the special nature of the domain structure, the domain walls of the crystal will move under the action of an external electric field, and adjacent domains will merge. This method can be used to obtain a single-domain relaxed ferroelectric single crystal.

[0116] Step 4.5: Slowly remove the voltage at a rate of 50 volts per minute, and place plane 3 and the plane parallel to it (i.e., perpendicular to it) Electrodes sputtered in a plane (direction) are wiped or ground off.

[0117] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0118] It should be understood that the above description is for illustrative purposes and not for limitation. Many embodiments and applications beyond the provided examples will be apparent to those skilled in the art upon reading the above description. Therefore, the scope of this teaching should not be determined by reference to the above description, but rather by reference to the foregoing claims and the full scope of their equivalents. For purposes of completeness, all articles and references, including patent applications and publications, are incorporated herein by reference. The omission of any aspect of the subject matter disclosed herein in the foregoing claims is not intended as a waiver of that subject matter, nor should it be construed as an indication that the applicant has not considered that subject matter as part of the disclosed inventive subject matter.

Claims

1. A method for preparing a single-domain relaxed ferroelectric single crystal, characterized in that, Includes the following processes: S1, electrodes are deposited on the two sides perpendicular to the two short sides of the optical surface of the cuboid relaxor ferroelectric single crystal, and then polarization treatment is performed at room temperature to obtain the engineered domain relaxor ferroelectric single crystal. Electrodes were sputtered on two sides perpendicular to the two short sides of the optical surface of the cuboid relaxor ferroelectric single crystal. A DC electric field was applied to the cuboid relaxor ferroelectric single crystal at room temperature. The electric field strength was 0.3-1 kV / mm, the voltage application rate was 3-50 V / min, the voltage was held for 5-30 minutes, and then the voltage was removed at a rate of 3-50 V / min. S2, electrodes are deposited on the two sides perpendicular to the two long sides of the optical surface of the engineering domain relaxor ferroelectric single crystal, and then polarization treatment is performed at room temperature to obtain a single-domain relaxor ferroelectric single crystal. Remove the electrodes from the engineered domain relaxor ferroelectric single crystal. Sputter electrodes on two sides perpendicular to the two long sides of the optical surface of the engineered domain relaxor ferroelectric single crystal. Apply a DC electric field to the engineered domain relaxor ferroelectric single crystal at room temperature with a field strength of 0.1-0.2 kV / mm and a voltage application rate of 3-10 V / min. Hold the voltage for 5-30 minutes, then remove the voltage at a rate of 3-50 V / min, and then remove the electrodes.

2. The method for preparing a single-domain relaxor ferroelectric single crystal according to claim 1, characterized in that, Before S1, the cuboid relaxor ferroelectric single crystal is annealed.

3. The method for preparing a single-domain relaxor ferroelectric single crystal according to claim 2, characterized in that, The annealing process is as follows: the cuboid relaxor ferroelectric single crystal is heated to 200-600℃ at a rate of 2-4℃ / min, held at that temperature for 5 hours, and then cooled to room temperature at a rate of 0.5-2℃ / min.

4. The method for preparing a single-domain relaxor ferroelectric single crystal according to claim 1, characterized in that, The relaxor ferroelectric single crystal in S1 is a binary (1-x)Pb(Mg) 1 / 3 Nb 2 / 3 Relaxor ferroelectric single crystals of O3-xPbTiO3 system, ternary (1-xy)Pb(In) 1 / 2 Nb 1 / 2 O3-xPb(Mg) 1 / 3 Nb 2 / 3 Relaxor ferroelectric single crystals of O3-yPbTiO3 system or rare earth-doped binary and ternary system relaxor ferroelectric single crystals.

5. The method for preparing a single-domain relaxor ferroelectric single crystal according to claim 1, characterized in that, The optical surface flatness of the relaxor ferroelectric single crystal in S1 is less than 1 μm.

6. The method for preparing a single-domain relaxed ferroelectric single crystal according to claim 1, characterized in that, The length of the relaxor ferroelectric single crystal in S1 is 2-10 mm, the width is 2-6 mm, and the height is 0.5-3 mm.

Citation Information

Patent Citations

  • Poling method for relaxor ferroelectric single crystal as nonlinear optical material

    CN107326443A